Maqashid Al-Shariah and Its Contribution to the Islamic Economy - Desta; Moh. Bahrudin; Syamsul Hilal (Neo Journal of economy and social humanities, 2025)
This study aims to analyze the definition of Maqashid Al-Sharia, both classical and contemporary, identify its background, and assess its contribution to the development of Islamic Economics. The method used in this study is a literature review with a normative juridical approach that examines the sources of classical and contemporary Islamic law relevant to the formulation of economic policy. The results of this study indicate that the sharia economy in the context of Maqashid Al-Sharia adheres to five basic cases (Al-kulliyat al-khams), namely maintaining religion (Hifz ad-din), maintaining the soul (hifdz an-nafs), maintaining reason (hifdz al-aql), and maintaining wealth (hifdz al-maal), which aims to create a fair and welfare-oriented economic system.